NETWORK PATTERNS AND COORDINATION OF UPSTREAM- DOWNSTREAM STAKEHOLDERS IN THE CORN AGRIBUSINESS CLUSTER - Haryono, Iranita; Qisti, Nurul; Akbar,; Rumallang, Ardi; Nadirah,; Padapi, Astrini; Nurwidah, Andi; Najah, Zulfatun (International Journal of Psychosocial Rehabilitation, 2020)
Agricultural development needs to be continuously developed to lead to the creation of an efficient, competitive farm, able to increase the income and standard of living of farmers especially corn agribusiness development. The purpose of this research is to describe the pattern of networks and coordination of upstream-downstream stakeholders in the corn agribusiness cluster. The research employed descriptive method. The results show that, the existence of agribusiness clusters provides great benefits in regional and national economic development in a more effective and efficient ways. There is no functional cooperation relationship between each level of upstream and downstream agricultural businesses. So, it is categorized into a relationship pattern.